THE EFFECT OF ISPO IMPLEMENTATION ON PALM OIL FARMERS' INCOME IN BANDAR PASIR MANDOGE, ASAHAN DISTRICT - Hasudungan Siregar; Yusniar Lubis; Syahbudin (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Indonesian Sustainable Palm Oil (ISPO) as an Indonesian-style sustainable palm oil certification system already has the principle of responsibility to workers or laborers, but in the field many companies have not implemented it. This study aims to find out and analyze how big the difference is in the level of production, price, income and use of production factors such as fertilization, use of pesticides and the labor of oil palm farmers who have ISPO and not ISPO in Bandar Pasir Mandoge District, Asahan Regency. This research method uses a quantitative approach. The research sample used in the study was 92 respondents, with the provisions of 46 ISPO farmers and 46 Non ISPO farmers. The analysis of this study was carried out using a different test (paired sample t-test). The results showed that there was a significant difference in the level of palm oil production that had ISPO and did not have ISPO in Bandar Pasir Mandoge District, Asahan Regency. There is a significant difference in the TBS price level of palm oil smallholders who have ISPO and not ISPO in Bandar Pasir Mandoge District, Asahan Regency. There is a significant difference in the level of income of palm oil farmers who have ISPO and not ISPO in Bandar Pasir Mandoge District, Asahan Regency. There are significant differences in the level of use of production factors such as fertilization, use of pesticides and workers who have ISPO and do not have ISPO in Bandar Pasir Mandoge District, Asahan Regency. There is a significant difference in the TBS price level of palm oil smallholders who have ISPO and not ISPO in Bandar Pasir Mandoge District, Asahan Regency. There is a significant difference in the level of income of palm oil farmers who have ISPO and not ISPO in Bandar Pasir Mandoge District, Asahan Regency. There are significant differences in the level of use of production factors such as fertilization, use of pesticides and workers who have ISPO and do not have ISPO in Bandar Pasir Mandoge District, Asahan Regency. There is a significant difference in the TBS price level of palm oil smallholders who have ISPO and not ISPO in Bandar Pasir Mandoge District, Asahan Regency. There is a significant difference in the level of income of palm oil farmers who have ISPO and not ISPO in Bandar Pasir Mandoge District, Asahan Regency. There are significant differences in the level of use of production factors such as fertilization, use of pesticides and workers who have ISPO and do not have ISPO in Bandar Pasir Mandoge District, Asahan Regency.